Acute extreme hypocapnia and diabetic coma in an elderly patient after surgery: A case report - Strecker, Thomas; Siegle, Michaela; Bremer, Frank Felix (SAGE Open Medical Case Reports, 2024)
Hyperglycemia and diabetic ketoacidosis are serious and life-threatening emergencies in diabetes patients. Early recognition of the symptoms of these disorders and their management are essential. Therapy is adequate rehydration, insulin treatment, electrolyte replacement, and handling of the underlying causative disease. Herein, we present an 83-year-old male with an extremely altered blood gas analysis after a surgical procedure of his left hand due to a phlegmon and describe the successful treatment through intensive care.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Diabetes; hyperglycemia; hypocapnia; respiratory medicine; surgery